1st International & 2nd National Orthodontic Conference of Bangladesh Orthodontic Society (BOS) - Brief Report - Hossain, Md Zakir (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Abstract not found DOI: http://dx.doi.org/10.3329/bjodfo.v2i2.16167 Ban J Orthod & Dentofac Orthop, April 2012; Vol-2, No.2, 48-54